The Influence of Fair Value Measurement on the Pledge of Overconfident Major Shareholders Based on Multiple Regression and Fisher Test. (18th March 2021) - Wang, Wei; Qu, Xiao-Hui; Du, Jian-Ju; Zhu, Jia-Ming
Abstract : Adopting fair value measurement may bring more earnings fluctuations and induce irrational psychology and radical financing behavior of managers and major shareholders. Based on behavioral corporate governance theory, using the sample of A-share nonfinancial listed companies of China during 2015–2017, this paper empirically examines the regulatory effect of fair value measurement; that is, whether fair value measurement affects the company's financing decisions when major shareholders have irrational psychological characteristics, i.e., overconfidence. The study found that overconfident major shareholders increase the probability of equity pledge and increase the proportion of equity pledge; further inspection found that if the level of accrued earnings management is higher, the adjustment effect of fair value measurement is also higher; when the risk of stock price collapse is higher, fair value measurement obviously increases the probability and ratio of overconfident major shareholders' equity pledge. The above conclusions provide empirical evidence that fair value measurement has a positively regulatory effect on financing decisions of major shareholders.